Investigating the Role of Upward Comparisons and Self-compassion on Stigma in People With Acne: Cross-sectional Study - Kate Adkins; Paul G Overton; Julia Moses; Andrew Thompson (JMIR Publications, 2023)
BackgroundThe use of image-laden social media is hypothesized as being implicated in psychological distress in individuals with conditions affecting their appearance. However, relatively little is known about the mechanisms involved in this relationship. ObjectiveThis cross-sectional study examined the relationship between photo-orientated social media use and feelings of stigmatization in adults with acne, and tested whether upward skin comparisons mediate and self-compassion moderates this relationship. MethodsAdults (N=650) with acne symptoms completed web-based measures of social media use (daily Facebook or Instagram use, Facebook function use), self-compassion, skin appearance comparisons, and internalized stigmatization. ResultsModerated-mediation and mediation analyses indicated that there was a significant indirect effect of Facebook photo use on stigmatization, mediated by upward appearance comparisons (estimation of indirect effect 11.03, SE 5.11, 95% CI 1.19-21.12). There was no significant relationship between Instagram use and feelings of stigmatization (estimation of indirect effect 0.0002, SE 0.005, 95% CI −0.011 to 0.009), yet upward appearance comparisons predicted feelings of stigmatization (B=0.99, P<.001). Self-compassion did not moderate the indirect or direct relationships between photo-orientated social media use and stigma. However, self-compassion was negatively correlated with upward appearance comparisons and feelings of stigmatization in both Facebook and Instagram users. ConclusionsThe way that individuals engage with social media, and in particular make appearance comparisons, should be considered when working with individuals with skin-related distress. Interventions aimed at boosting self-compassion and reducing appearance comparisons may provide avenues for protecting against feelings of stigma.